FORMATION OF AN INTERNAL MANAGEMENT REPORTING SYSTEM IN DAIRY FARMING - ZDYRKO, Nataliya; FILIPOVA, Oleksandra (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The current state of dairy farming in Ukraine is characterized by a number of problems, among which the issue of production management efficiency is particularly acute. The underdeveloped system of internal management reporting is one of the key factors hindering the development of the industry. The relevance of the problem of lack of clear rules in the formation of an internal management reporting system in dairy farming is established. The main problems and statistics of the reduction in the number of cattle are considered, the tendency to reduce the number of cattle in percentage terms is calculated. The number of cattle is presented, taking into account farms of all categories, enterprises and households for the years 2010-2024 as of January 1. It is noted that internal reporting is a necessary tool for successful enterprise management, which provides management with reliable and timely information about business activities, allows to investigate the causes of errors and ways to correct them. It was determined that the Internal management reporting of dairy cattle breeding and agricultural production is not regulated by normative and legislative acts, therefore its form and content is determined by each enterprise independently, depending on the field of production. A modern system of internal reporting will help Ukrainian milk producers to improve product quality and production efficiency, which, in turn, will make them more competitive on the market. Regular data analysis will allow identifying and eliminating problems, and detailed information about production processes will ensure compliance of products with modern standards. The role of management accounting in reducing the cost of dairy farming is analyzed. The basic requirements for internal management reporting in agriculture are summarized. The results of the study can be used to develop recommendations for improving management systems on dairy farms and increasing their competitiveness. The introduction of standardized forms of internal reporting in dairy farming is a key factor in improving the efficiency of the industry’s management. The proposed organizational solutions will ensure better and more timely reporting, which, in turn, will facilitate informed management decisions.